(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Spatial clustering analysis is a significant spatial data mining technique. It separates objects into clusters as per their likenesses in both area and traits perspectives. It assumes a fundamental function in density appropriation ID, hot-spot detection, and trend discovery. Spatial clustering algorithms in the Euclidean space are moderately adult, while those in the organization space are less well-informed. Spatial data mining is the use of data mining techniques to spatial data. Data mining all in all is the quest for concealed examples that may exist in huge databases. Spatial data mining is the discovery of intriguing the relationship and qualities that may exist certainly in spatial databases. This paper planned to introduce a notable clustering calculation, named density-based spatial clustering of utilizations with clamour (GRID DBSCAN), to organize space and proposed another clustering calculation named network space DBSCAN (GRID-DBSCAN). For this reason, clustering is one of the most important strategies in spatial data mining. The principle bit of leeway of utilizing clustering is that fascinating structures or clusters can be found straightforwardly from the data without utilizing any earlier information. This paper presents an outline of density based strategies for spatial data clustering.